Overexpression of MMP-3 and uPA with Diminished PAI-1 Related to Metastasis in Ductal Breast Cancer Patients Attending a Public Hospital in Mexico City - Luis Miguel Barajas-Castañeda; Evelin Cortés-Gutiérrez; Francisco Mario García-Rodríguez; Rafael Campos-Rodríguez; Eleazar Lara-Padilla; Fernando Enríquez-Rincón; María Eugenia Castro-Mussot; Paula Figueroa-Arredondo (Journal of Immunology Research)
Extracellular matrix metalloproteases and the fibrinolytic system are important protease systems interacting with each other in charge of remodeling and recycling of tissues. Their role in tumor invasion and metastasis is often discussed. In this study several metalloproteases such as MMP-1, MMP-3, MMP-9, and TIMP-1 together with molecules from the fibrinolytic system like uPA, its receptor uPAR, and its inhibitor, PAI-1, were studied by immune-histochemistry to establish a comparison with and without metastasis. From the (118) primary tumors of Mexican patients with ductal breast cancer studied, 56% were grade II and 69% were size T2; the group with metastatic ganglia included 64 samples (54.3%). In patients with metastasis the estimated expression of MMP-3 and uPA (resp., 28% and 45%) was higher than that from no metastatic tumors; it means there is higher expression of both markers in metastatic tumors (p<0.05). At the same time, metastatic tumors showed statistically significant lower signal of PAI-1 (24%) than tumors without metastasis (p<0.05). We concluded that overexpression of MMP-3 and uPA, altogether with diminished expression of PAI-1 from metastatic tumors, might be a crucial step towards metastasis in ductal breast cancer. Nevertheless, additional studies in different populations are necessary to establish a pattern.